2009
DOI: 10.1590/s0037-86822009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Flebótomos de áreas com ocorrências de casos humanos de leishmaniose tegumentar americana no Município de Seropédica, Estado do Rio de Janeiro

Abstract: A leishmaniose tegumentar americana é causada por protozoários do gênero Leishmania, que acomete a pele e mucosa; é primariamente uma infecção zoonótica. Inquéritos flebotomínicos foram realizados em quatro áreas com ocorrência de casos humanos de leishmaniose tegumentar americana do município de Seropédica. Utilizou-se a metodologia de coleta com capturas manuais no horário das 18 às 22h, durante 12 meses consecutivos. No período de outubro de 2004 e setembro de 2005, capturamos 2.390 exemplares pertencentes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
(7 reference statements)
1
6
0
2
Order By: Relevance
“…This result is consisted with that of Cardoso et al (2009), who observed a high prevalence of Lu. intermedia, which is anthropophilic and adapted to disturbed environments (AGUIAR et al, 1996;TOLEZANO, 1994), in two villages located in these areas.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…This result is consisted with that of Cardoso et al (2009), who observed a high prevalence of Lu. intermedia, which is anthropophilic and adapted to disturbed environments (AGUIAR et al, 1996;TOLEZANO, 1994), in two villages located in these areas.…”
Section: Resultssupporting
confidence: 69%
“…in drier areas and banana plantations of the municipality of Itaguaí (AGUIAR et al, 1996), bordering Seropédica. In Seropédica, areas where human and dog cases were registered, Cardoso et al (2009) reported a predominance of Lu. intermedia followed by Lu.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the three municipalities where the animals lived, the highest seropositivity was found in Seropedica, followed by Itaguai and Mangaratiba. In a study performed by Cardoso et al (2009) in Seropedica, species of sandflies vectors of cutaneous leishmaniasis were captured, suggesting that these species are potential vectors of leishmaniasis in the municipality and that dogs should be considered potential reservoirs of this parasite due to the high frequency of seropositivity detected. Souza et al (2009) and Aguiar et al (1996), analyzing sandflies in the green coast of the State of Rio de Janeiro, found some species of great epidemiological importance.…”
Section: Discussionmentioning
confidence: 99%
“…(N.) whitmani, which is incriminated as one of the vectors of Leishmania (Viannia) braziliensis, the most prevalent parasite infecting humans and one of the main species involved in American cutaneous leishmaniasis (ACL) in Brazil, is also associated with the presence of domestic animals 6,11,13 . Studies carried out in areas of ACL transmission in Minas Gerais have found L. (N.) whitmani displaying great behavioral flexibility, anthropophilic activity in surrounding woods and around human dwellings, where it may be developing hematophagous habits involving humans and domestic animals 14,17 .…”
Section: Discussionmentioning
confidence: 99%